Root-associated fungi from Greenland - Abarenkov, Kessy; Somervuo, Panu; Nilsson, R. Henrik; Kirk, Paul M.; Huotari, Tea; Abrego, Nerea; Ovaskainen, Otso (Dryad Digital Repository, 2018)
Fungal ITS2 sequence data of root-associated fungi from Greenland in fasta format. DNA extracted from different plant species roots collected along the altitudinal gradient of Aucella mountain in the Zackenberg valley.